Differentiation and the brain : how neuroscience supports the learner-friendly classroom - Sousa, David A.; Tomlinson, Carol A. (Solution Tree, 2018)
Students are becoming more academically and culturally diverse, making it more important than ever to shift away from a one-size-fits-all approach and toward differentiated instruction. The second edition of this best-selling book will help you create truly effective, brain-friendly classrooms for all learners. The authors share an array of updated differentiated instruction examples, scenarios, and exercises, as well as the latest educational psychology research from cognitive psychology, neuroscience, and pedagogy.